A New Graphdiyne Nanosheet/Pt Nanoparticle‐Based Counter Electrode Material with Enhanced Catalytic Activity for Dye‐Sensitized Solar Cells. Issue 12 (13th April 2015) - Ren, Hao; Shao, Hui; Zhang, Lijuan; Guo, Dong; Jin, Quan; Yu, Ranbo; Wang, Lei; Li, Yuliang; Wang, Yun; Zhao, Huijun; Wang, Dan
<x xml:space="preserve">Abstract</x> A graphdiyne nanosheet/Pt nanoparticle composite shows outstanding catalytic activity for the reaction of I3−/I− redox pairs, i.e., the best among rGO/Pt nanoparticle composites, Pt nanoparticles and Pt foils. This is ascribed to enhanced electron transfer resulting from the easier chemical interaction between Pt and the triple bond of graphdiyne.